PEMIKIRAN PROF. DR. H. BUSTHANUL ARIFIN, SH TENTANG PENINGKATAN WEWENANG PENGADILAN AGAMA DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH DI INDONESIA: Sekolah Tinggi Agama Islam Negeri (STAIN) Mandailing Natal - TENTIYO SUHARTO (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2020)
Abstract History of the formation of Law Number 7 of 1989 concerning the Religious Courts is a long struggle by Muslim leaders and experts in Islamic law in Indonesia, one of whom is Prof. Dr. H. Busthanul Arifin, S.H continues to think seriously about making Islamic law an integral part of the national legal system. According to Prof. Dr. H. Busthanul Arifin, S.H. The Indonesian nation is said to be a country with a majority Muslim population, but the community has not been able to freely implement Islamic syari'at values ??in public relations so that it can be said that Islamic syari'at values ??are very difficult to convey. This type of research is library research (Library Research) and this research is a character study research with inductive descriptive analysis. According to Busthanul Arifin the authority and power of the Religious Courts by referring to the explanation of article 49 of Law Number 50 of 2009 concerning Amendments to Law Number 7 of 1989 and Amendments to Law Number 3 of 2006 concerning Religious Courts are Marriage, Inheritance, Will, Grants, Endowments, Zakat, Infaq, Shadaqah and Syari'ah Economics. With the Constitutional Court's decision, there will be no more dualism in the settlement of Islamic Banking disputes. This is in line with Law Number 21 of 2008 concerning Islamic Banking. The Religious Courts are the only courts authorized to resolve sharia banking disputes. Keywords: Law, Religious Courts, Islamic Law, Figure, Busthanul Arifin, National Law, Sharia, Disputes, Constitutional Court, Sharia Banking, Sharia Economics